1992
DOI: 10.1177/002224299205600303
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Women in Industrial Selling: A Decade of Change

Abstract: The rapid influx of women into the industrial salesforce over the last decade has created a need to upgrade understanding of the female salesperson. The authors examine gender differences in job-related attitudes and performance outcomes in an integrated salesforce. Results showing few gender differences bring into question anecdotal suggestions that women require special programs to facilitate their assimilation into the salesforce. Specific recommendations are provided about individual treatment for both mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…While commitment was associated with seniority in this study, there was no difference between men and women in their commitment to work. Our results thus support previous research which found no difference in organisational commitment between women and men (Kacmar et al 1999;Martin and Hafer 1995;Moncrief et al 2000;Schul and Wren 1992;Siguaw and Honeycutt 1995;van der Velde et al 2003).…”
Section: Discussionsupporting
confidence: 92%
“…While commitment was associated with seniority in this study, there was no difference between men and women in their commitment to work. Our results thus support previous research which found no difference in organisational commitment between women and men (Kacmar et al 1999;Martin and Hafer 1995;Moncrief et al 2000;Schul and Wren 1992;Siguaw and Honeycutt 1995;van der Velde et al 2003).…”
Section: Discussionsupporting
confidence: 92%
“…For example, earlier findings in sales contexts showed no significant gender differences in various job satisfaction dimensions, but indicated that females displayed lower levels of role clarity than males (Busch and Bush, 1978). Schul and Wren (1992) reported that female salespeople had higher satisfaction with supervision than males. They also reported that male salespeople had greater role conflict than their female counterparts, while there was no gender difference in role ambiguity.…”
Section: Gender-based Differencesmentioning
confidence: 90%
“…Research into gender differences in boundary-spanning employees' workplace attitudes and behaviors has a long tradition (Babin and Boles, 1998;Moncrief et al, 2000;Schul and Wren, 1992). Two observations surface from a synthesis of these writings.…”
Section: Introductionmentioning
confidence: 99%
“…Swan, Rink, I s e r , & Martin, 1984). For instance, by the early 1980s women held approximately 23% of all professional selling jobs (Dawson, 1992;Schul & Wren, 1992) and about 20% of industrial buying positions (Swan, er al., 1984).…”
Section: Samplementioning
confidence: 99%
“…A question of ethicality surrounding corporate-gift giving behavior, however, may impede the effectiveness of gifts as a relationship-building tool. Furthermore, the increasing number of sales and purchasing positions across a variety of business organizations are held by women (Schul & Wren, 1992) has led to the realization that the feminization of the industrial sales profession may change the ethical standards of the profession (Dawson, 1992). Studies examining differences in ethical perceptions or behaviors between men and women have produced mixed results (cf.…”
mentioning
confidence: 99%